Studi Asosiasi Kepiting (Brachyura) dengan Mangrove di Kecamatan Kamal Kabupaten Bangkalan Madura - Siti Aisyah; Diana Hernawati; Rinaldi Rizal Putra (Jurnal Biosilampari : Jurnal Biologi, 2023)
Kamal District has a mangrove ecosystem area which is a habitat for marine life, including crabs. This study aims to determine the association of Crabs with Mangroves in Kamal District, Bangkalan Regency, Madura. This research uses quantitative methods with the type of survey research and the technique used is purposive sampling. The sampling method uses ladder transect. Based on the results, mangrove data were obtained which were classified into 4 families, 4 genera and 7 species. While crabs consist of 2 families, 4 genera and 4 species. The average value of the mangrove ecological index consists of a diversity index of 1.28 in a medium category, a uniformity index of 0.66 in a high category and a dominance index of 0.32 in a medium category. The average value of the Crab ecological index consists of a diversity index of 1.24 in a medium category, a uniformity index of 0.89 in a high category and a dominance index of 0.32 in a medium category. The result of the ꭓ2 test are that there are 4 positive associations, 2 negative associations and 22 no associations.